Parallel lives or interconnected histories? Anagarika Dharmapala and Muhammad Barkatullah's 'world religioning' in Japan. (July 2022) - Siddiqui, Samee
Abstract: This article compares the ideas, connections, and projects of two South Asian figures who are generally studied separately: the Indian pan-Islamist Muhammad Barkatullah (1864–1927) and the Sinhalese Buddhist reformer Anagarika Dharmapala (1864–1934). In doing so, I argue that we can understand these two figures in a new light, by recognizing their mutual connections as well as the structural similarities in their thought. By focusing on their encounters and work in Japan, this article demonstrates how Japan—particularly after defeating Russia in the Russo-Japanese War in 1905—had become a significant site for inter-Asian conversations about world religions. Importantly, exploring the projects of Barkatullah and Dharmapala makes visible the fact that, from the late nineteenth century until the outbreak of the First World War, religion played a central role—alongside nationalism, race, and empire—in conversations about the possible futures of the international order.